The story of the Navajo - Gridley, Marion Eleanor, 1906-; Glaubke, Robert (New York, Putnam, 1971)
Traces the history of the Navajo people, retells some of their legends, and compares their ancient and modern way of life.
Keywords: Navajo Indians -- Juvenile literature; Navajo Indians; Indians of North America -- Southwest, New